Seroprevalence of Borrelia, Anaplasma, Bartonella, Toxoplasma, Mycoplasma, Yersinia, and Chlamydia in Human Population from Eastern Poland - Angelina Wójcik-Fatla; Anna Sawczyn-Domańska; Anna Kloc; Joanna Krzowska-Firych; Jacek Sroka (Pathogens)
The epidemiological situation related to infectious diseases is influenced by many factors. To monitor actual trends in selected zoonoses, a total of 473 serum samples from farmers, forestry workers, and veterinarians were collected for serological examination. Anti-Borrelia burgdorferi sensu lato (s.l.) antibodies were tested with ELISA and Western blot (WB) tests; the detection of anti-Toxoplasma gondii antibodies was performed using an enzyme linked fluorescence assay (ELFA). Antibodies to bartonellosis, anaplasmosis, and chlamydiosis were determined by indirect immunofluorescent test (IFA), whereas antibodies to yersiniosis and mycoplasmosis were confirmed in the ELISA test. Positive or borderline results of antibodies against B. burgdorferi s.l. in the ELISA test were detected in 33.8% of the study population. The borderline or positive ELISA test results for at least one antibody class were confirmed by WB in 58.7% of cases. The IgG antibodies against Anaplasma phagocytophilum, Toxoplasma gondii, and Mycoplasma pneumoniae were detected in 9.6%, 51.7%, and 63.6% of samples, respectively. Antibodies against Yersinia spp., Bartonella henselae, and Chlamydia pneumoniae were found to vary between 43 and 47%.